The Effect Of Service Quality On Customer Satisfaction At Eureka Coffee In Pinrang City - Safariani R, Nur; Haeruddin, Muh. Ikhwan Maulana; Musa, Muh. Ichwan; Hasbiah, Siti; Aswar, Nurul Fadilah (Jurnal Intelek Insan Cendikia, 2024)
This study aims to determine the physical evidence, reliability, responsiveness, assurance and empathy affect customer satisfaction at Eureka Coffee. This research is quantitative research. The population in this study were all visitors to Eureka Coffee who visited from January to July 2023 totaling 1,536 visitors, using the Sampling method obtained a sample of 100 respondents. The data collection technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS) v. 23. The results of this study indicate that physical evidence (X1) partially has a positive and significant effect on customer satisfaction at Eureka Coffee. Reliability (X2) partially has a positive and insignificant effect on customer satisfaction at Eureka Coffee. Responsiveness (X3) partially has a positive and insignificant effect on customer satisfaction at Eureka Coffee. Assurance (X4) partially has a positive and insignificant effect on customer satisfaction at Eureka Coffee. Empathy (X5) partially has a positive and significant effect on customer satisfaction at Eureka Coffee. As well as physical evidence, reliability, responsiveness, assurance and empathy simultaneously have a positive and significant effect on customer satisfaction at Eureka Coffee.